Evaluasi Rasionalitas Terapi Antibiotik Pada Faringitis Akut di Puskesmas Kota Denpasar - Manik Partha Sutema, Ida Ayu; Sukmantari, Pande Ni Nuhung; Windidaca Brata Putri, Dhiancinantyan (Pengurus Pusat Ikatan Apoteker Indonesia, 2022)
Pharyngitis is an inflammatory disease of the throat caused by viruses (70-90%) and bacteria (10-30%), and one of the diseases that is ranked third in the pattern of the 10 most common diseases in Puskesmas 2017. Appropriate therapy in pharyngitis is still lacking, where antibiotic therapy is still very high in children. This study was conducted to determine the rationality of antibiotic therapy in acute pharyngitis based on the centor score and to see the description of the suitability of the dose, indication, time of administration, frequency of administration and the presence of drug side effects. The design of this study used descriptive analysis with a cross-sectional retrospective method. Data collection was carried out by collecting samples derived from secondary data by observing pharyngitis patient medical record data at the Denpasar City Health Center in February - April 2022. The inclusion criteria of this study were complete and readable medical records in children aged 3-14 years. Results showed that giving antibiotics based on suitability for centor criteria showed that 70.22% of cases in this study were still not giving antibiotics correctly based on the score obtained. Based on the appropriateness of the use of antibiotics seen from the criteria for dosage, indication, time of administration, frequency of administration and warning of drug side effects, the results obtained were as many as (39.40%) doses that were inappropriate because the dose received was lower than the dose stated in the literature, the duration of antibiotic administration 86.36% of patients who did not use the right antibiotic, and all patients had the right frequency of using antibiotics and none experienced drug side effects. The rationality of giving antibiotics for pharyngitis is still not in accordance with the Puskesmas guidelines using centor criteria. Suggestions need to be evaluated against the use of antibiotics in pharyngitis in an effort to reduce the use of antibiotics in accordance with centor criteria.